1975
DOI: 10.1016/0092-8674(75)90158-0
|View full text |Cite
|
Sign up to set email alerts
|

Methylated nucleotides block 5′ terminus of HeLa cell messenger RNA

Abstract: Polyadenylylated [poly(A)+] mRNA from HeLa cells that were labeled with [3H-methyl]-methionine and 14C-uridine was isolated by poly(U)-Sepharose chromatography. The presence of approximately two methyl groups per 1000 nucleotides of poly(A)+ RNA was calculated from the 3H/14C ratios and known degrees of methylation of 18S and 28S ribosomal RNAs. All four 2'-O-methylribonucleosides, but only two base-methylated derivatives, 7-methylguanosine (7MeG) and 6-methyladenosine (6MeA), were identified. 6MeA was the maj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
654
1

Year Published

1979
1979
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 683 publications
(671 citation statements)
references
References 11 publications
16
654
1
Order By: Relevance
“…N 6 -adenosine methylation (m 6 A) is the most abundant RNA modification found in ϳ25% of RNA species in mammalian cells (1,2). Despite its discovery decades ago (3)(4)(5)(6)(7), the biochemical pathways responsible for m 6 A and the biological functions of this process were not fully defined until very recently (8)(9)(10). Three methyltransferases, including methyltransferase-like 3 (METTL3), methyltransferase-like 14 (METTL14), and Wilms' tumor 1-associated protein (WTAP), act as m 6 A writers and catalyze RNA m 6 A at specific sites with the consensus sequence [(G/A)GAC, where the underlined adenosine is the methylation site] (11,12).…”
mentioning
confidence: 99%
“…N 6 -adenosine methylation (m 6 A) is the most abundant RNA modification found in ϳ25% of RNA species in mammalian cells (1,2). Despite its discovery decades ago (3)(4)(5)(6)(7), the biochemical pathways responsible for m 6 A and the biological functions of this process were not fully defined until very recently (8)(9)(10). Three methyltransferases, including methyltransferase-like 3 (METTL3), methyltransferase-like 14 (METTL14), and Wilms' tumor 1-associated protein (WTAP), act as m 6 A writers and catalyze RNA m 6 A at specific sites with the consensus sequence [(G/A)GAC, where the underlined adenosine is the methylation site] (11,12).…”
mentioning
confidence: 99%
“…Recent work has demonstrated an important role for the methylation of adenosines (m 6 A) in mRNA in the regulation of stem cell pluripotency (36)(37)(38). m 6 A is the most common internal modification to mRNA in mammalian cells (39)(40)(41), yet little was known about the biology of this modification until a recent flurry of research led to the identification of the enzymes that add and remove m 6 A (METTL3/METTL14 and FTO/ALKBH5, respectively) (42)(43)(44), as well as enrichment-based sequencing experiments to identify mRNAs modified by m 6 A (45,46). With respect to stem cell pluripotency, it has been shown that reduced m 6 A levels promote pluripotency (36)(37)(38).…”
mentioning
confidence: 99%
“…However, in these same mammalian cells both cap 1 and cap 2 structures have been noted in cytoplasmic mRNA (16,18,37,39). In the sea urchin embryo only cap 1 is present in cytoplasmic mRNA, as in its counterpart hnRNA (22).…”
Section: Methodsmentioning
confidence: 98%
“…The 3' terminal poly (A) sequence is present among a certain fraction of hnRNA molecules (11,12) and also among only a fraction of mRNAs (13,14). The 5' terminal cap, consisting of a m7G joined to the penultimate nucleotide through a 5'-5 ' triphosphate bridge, is ubiquitous among eukaryotic mRNAs (15)(16)(17). The cap structure has also been detected in hnRNA (18,19).…”
Section: Introductionmentioning
confidence: 96%